Does the Addition of Seashell or Zirconium Oxide Nanoparticles at Different Concentrations Improving Tensile Bond Strength of Orthodontic Adhesive? In-vitro study. - Alaa Gharis Adnan; Neam Agha (University of Mosul, College of Dentistry, 2024)
Aims: The study aimed to assess the tensile bond strength of modified-Heliosit orthodontic adhesive with different concentrations of seashell or zirconium oxide nanoparticles. Materials and methods: Thirty-five sound-extracted human premolars were collected. Hydroxyapatite nanoparticles were manually prepared from natural snail seashells. Heliosit orthodontic adhesive was modified by (8%, 10%, and 12% seashell), and (1%, 3%, and 5% zirconium oxide) nanoparticles. Standard edgewise brackets were bonded to buccal enamel surfaces of the samples of control and six modified adhesive groups. At 24 h after bonding, tensile bond strength was measured. The adhesive remnant index was scored under (10X) magnification power of the stereomicroscope after de-bonding. The chemical characteristics of orthodontic adhesive material were explored before and after mixing with seashell and zirconium oxide nanoparticles by using Fourier Transform Infrared Spectrometry. Results: Seashell groups (8, 10, & 12 %) containing hydroxyapatite nanoparticles and zirconium oxide nanoparticles groups (1%, 3%, and 5%) had a higher tensile bond strength mean value than the control group, (10%) seashell group had the highest mean value, while the least mean value was in the control group with statistically significant differences between them. Regarding the adhesive remnant index, no significant differences were found among the studying groups. Conclusions: the addition of (10%) seashell nanoparticles had the best performance and improved the tensile bond strength of Heliosit orthodontic adhesive without violating the remnant of adhesive on the buccal enamel surface after brackets de-bonding or inducing any chemical reactions with the resin adhesive.